A Simplistic Method for Assessing Seismic Damage in Rock Tunnels Before Earthquake: Part 2—Application of Simplistic Method by a Python-Based GUI Tool for India and Adjacent Countries - Reddy, A. Dinesh; Singh, Aditya (Rock mechanics and rock engineering, 2025)
The first part of this paper outlines a simple method for assessing seismic damage to rock tunnels prior to an earthquake, based on the Seismic Damage Classification of Tunnels (SDCT), proposed by Reddy and Singh (2024) [‘A Simplistic Method for Assessing Seismic Damage in Rock Tunnels Before Earthquake: Part 1—Damage Prediction and Validation Using Seismic Damage Classification of Tunnels’, Rock Mechanics and Rock Engineering, pp. 1-32]. However, to implement the proposed methodology in the field, the data on seismic sources within 250 km are necessary. Seismic sources within this range should be mapped in Google Earth Pro to obtain source-to-site distances, which are then used to calculate PGA values. After gathering all inputs, the engineer needs to check critical parameter combinations to determine damage class and predict damages before an earthquake. Though the method is simple, the process is time-intensive, requiring precision at each step. This study simplifies the process and develops a software implementation of the proposed methodology. This software is an outcome of a Python-based GUI tool developed for India and adjacent countries. To develop this tool, the seismic sources are collected and mapped in QGIS to create a database of 4602 faults across India and adjacent countries. The written Python code identifies the sources within 250 km of the tunnel site and also calculates the PGA from each source through empirical attenuation relationships. This GUI tool evaluates the Seismic Vulnerability of Rock Tunnels (SVRT) using input parameters, such as latitude, longitude, Rock Mass Rating, Overburden, lining type, and tunnel shape. Using the obtained PGA values for seismic sources within 250 km and by critically combining the entered input parameters, the tool predicts the damage class and probable damages for any location within the study region. The reports are generated in .txt (notepad) format and graphs for the distribution of total faults in each damage class are provided for the user’s location. The validation of this tool is done by performing SVRT of the Daliang tunnel site. The results of the software and actual damages of the Daliang tunnel due to the Menyuan earthquake (2022/Mw 6.6) in Qinghai, China are compared. The tool showed a good agreement with the proposed software. The software’s user-friendly interface makes it easy to input data and quickly obtain results. Highlights For the first time, a simple method is proposed for predicting and assessing the seismic damages to the rock tunnels before an earthquake using the Seismic Damage Classification of Tunnels. Employing the methodology, this study proposes a software, which is a Python-based GUI tool that can perform the Seismic Vulnerability of Rock Tunnels (SVRT) before an earthquake in India and adjacent Countries. Utilizing this tool, engineers can perform the SVRT for tunnel sites by generating reports and graphs before an earthquake. The proposed software is simple to use and delivers quicker results through obtained reports, as it can be used by engineers for preliminary seismic investigations.